Biomarker patterns in a time-resolved holocene/terminal Pleistocene sedimentary sequente from the Guadiana river estuarine area (SW Portugal/Spain border) - González-Vila, Francisco (2013)
The vertical distribution of terrestrial and phytoplankton biomarker compounds in a sediment core from the coastal estuarine zone of the Guadiana river (southwest border between Portugal and Spain) was determined by gas chromatography–mass spectrometry. Significant downcore fluctuations were observed in the patterns of the most abundant alkyl series (n-alkanes and n-fatty acids), as well as in several biomarker ratios. In addition, a specific contribution from conifers is reflected in the presence of a resin acid series that first appears 6500 years BP. The observed changes in the lipid assemblage within the Holocene suggest recent variations in the planktonic and terrigenous supply, which are attributed mainly to the evolution of the circulation pattern in the estuary and to the alteration of vegetation cover within the Guadiana drainage basin. Our data suggest that on a 103–104 year time-scale, little or no diagenetic change occurred with respect to the compounds in question.